A prática dos assistentes sociais do setor de assistência social (SAS) da Província Marista do Brasil Centro-Sul: sua relação com os princípios e diretrizes da política nacional de assistência social (PNAS) - Barbosa, Marco Antonio (2007)
This dissertation is about the existant afinity relation between the principles and directions of the National Social Assistance Policy and the Central South Maristas do Brazil Province Social Assistance, from social assistants professional pratices studies form social units of assistance sector, anchored in colected data analysis result in semi structured interviews in documented and and bibliographical studies. We base this research in the Marxist theory, including Michael Löwy contribuition, in relation to totalitary category. We aim at learning, in a sequential proximity process, the object movement, its afinity proceeding. The studies made from social assistant practices, in the constitution of this afinity relation, took us, therefore, to a complex dynamic, proper from the social net constitution, resulted from strengh and facing different and distinct realities that make a unit in diversity, a dynamic totality changing. We, therefore conclude, that afinity between the Social Assistant Institutional Policy and PNAS express a dynamic movement in changing in which the way we estabilish the interactions are determined and determine the afinity constitution